2007
DOI: 10.1021/jp0742721
|View full text |Cite
|
Sign up to set email alerts
|

Six Single-Crystal Structures Showing the Dehydration, Deamination, Dealumination, and Decomposition of NH4+-Exchanged Zeolite Y (FAU) with Increasing Evacuation Temperature. Identification of a Lewis Acid Site

Abstract: Single crystals of zeolite Y, |Na 71 |[Si 121 Al 71 O 384 ]-FAU, with diameters up to 0.20 mm were grown. They were ion exchanged to generate |(NH 4 ) 64 Na 5 K 2 |[Si 121 Al 71 O 384 ]-FAU. Crystals 1 through 6, respectively, were vacuum dehydrated at 323, 373, 423, 473, 523, and 573 K, and without reexposure to the atmosphere, their structures were determined crystallographically at 294 K using synchrotron X-radiation. Their compositions (best integers) are seen to be respectively |(NH 4 ) 59 H 5 Na 5 K 2 (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 57 publications
(115 reference statements)
7
48
3
Order By: Relevance
“…Further description on the synthetic procedure is available in reference. 19 The product was characterized by optical microscopy, SEM, and single-crystal X-ray technique analysis. Microscopic examination showed that the single crystals were colorless and transparent.…”
Section: å)mentioning
confidence: 99%
“…Further description on the synthetic procedure is available in reference. 19 The product was characterized by optical microscopy, SEM, and single-crystal X-ray technique analysis. Microscopic examination showed that the single crystals were colorless and transparent.…”
Section: å)mentioning
confidence: 99%
“…They have been widely studied and used as ion exchangers, adsorbents and catalysts in industrial processes, because of the properties originated from the unique crystal structure containing large pore size and void volume [1]. ion at Ba1' is located at site 1' in the sodalite cavities opposite D6Rs; the Ba 2+ ion was recessed by 1.32 Å into the sodalite cavity from their 3-oygen plane.…”
Section: Discussionmentioning
confidence: 99%
“…Large single crystals of sodium zeolite Y(FAU), stoichiometry Na 71Si121Al71O384 per unit cell, were prepared by Lim et al [1]. One of these, aclear colorless octahedron about 0.22 mm in crosssection was lodged in aP yrex capillary.…”
Section: Source Of Materialsmentioning
confidence: 99%
“…The positions of the cations would be determined in the fully dehydrated materials. [31][32][33]. Each was lodged in Pyrex capillary, one in each.…”
Section: Objectivementioning
confidence: 99%